The Church and the transmission of the faith in the horizon of the new evangelisation - Madrigal Terrazas, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This article studies the relation between the mission of the Church and the transmission of the faith taking as a point of reference the text of the lineamenta for the XIII Synod’ Bishops ordinary Assembly, following its three chapters: time of new evangelisation, to proclaim the Gospel of Jesus Christ, to initiate to the Christian experience.